Prevalence of dental carries among school-going children aged 7-13 years in Kabul City - Ahmad Khalid Aalemi; Bentulhuda Yaqubi (BMC, 2024)
Abstract Background Dental caries is a major, multifactorial oral condition that causes the demineralization of tooth enamel and impacts approximately half of the world's child population. This study aimed to determine the prevalence of dental caries among school-going children aged 7 to 13 years in Kabul city. Methods This descriptive cross-sectional study was conducted with 491 students aged 7 to 13 years in Kabul during the first half of 2019. A multistage cluster sampling method was used, in which educational zones, schools, and classes were selected. The data were collected using pre-structured questionnaires through face-to-face interviews and oral examinations of students using dental probes and mouth mirrors while adhering to infection control protocols. The collected data were analyzed using Statistical Package for Social Science version 21.0, and a p-value < 0.005 was considered as statistically significant. Results The average age of the study participants was 9.9 ± 1.8 years. Boys made up approximately 45% of the participants, while 54.8% were girls. The overall prevalence of dental caries was 78.8%, with 62.1% in deciduous teeth and 42.8% in permanent teeth. Among students who did not brush their teeth, the prevalence of dental caries was 84.8%, compared to 81.7% for those who brushed once daily, 78.7% for those brushing twice daily, and 67.4% for those brushing three times daily (p = 0.022). About 10% of students had dental calculus, with a prevalence of 17.0% among those aged eleven and older, 10.0% among students aged nine to ten years, and 5.9% among students aged eight and younger (p = 0.006). Poor oral hygiene affected nearly one-third of the students, with 34.2% among boys and 30.9% among girls. Poor oral hygiene was more prevalent in students aged eight and younger (38.8%) compared to those aged eleven and older (25.9%) (p = 0.023). Conclusions The prevalence of dental caries among students aged 7 to 13 years in Kabul schools was similar to that in most developing countries. The prevalence of dental calculus was greater among students aged eleven years and older. Over 99% of the students surveyed had not undergone any dental treatment.